Photosensitive composition, composite, electronic component, and method for producing electronic component
By using a photosensitive composition of a conductive powder, a cellulose-based organic binder and a methacrylic photocurable resin in the manufacturing of electronic components, the problem of difficulty in improving the development and resolution of the conductive layer is solved, and the problem of achieving the problem of simultaneously improving the development of the conductive layer is achieved. The stable formation and production efficiency of the conductive layer are improved by miniaturizing and high-density.
Patent Information
- Application Number
- CN201910217714.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-23
- Filing Date
- 2019-03-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-04-06
AI Technical Summary
Prior Art In the manufacture of electronic components, it is difficult to achieve high levels of development and resolution of the conductive layer simultaneously, especially in electronic devices requiring smaller size and higher density, the increase in the thickness of the conductive layer will lead to insufficient curing and The problem of peeling, the development time is prolonged when the line spacing is small, and the residue is difficult to completely remove.
By adjusting the ratio of these components, the photosensitive composition is adopted to balance the development and resolution, which includes a conductive powder, a cellulose-based organic binder, a methacrylic photocurable resin with an acid value, and a photopolymerizable compound. Improve the adhesion and stability of the conductive layer to ensure the formation of conductive layer under small line width and high density.
The stable formation of the conductive layer under small line width and high density conditions is achieved, which shortens the development time, reduces residue, improves the adhesion and productivity of the conductive layer, and is suitable for forming a thin line conductive layer with an L/S of 20 μm/20 μm or less.
Smart Images

Figure BDA0002002591140000191 
Figure BDA0002002591140000221 
Figure HDA0002002591150000011
Abstract
Description
Technical Field
[0001] The present invention relates to a photosensitive composition and its use, and more particularly to a photosensitive composition, a composite, an electronic component, and a method for producing the electronic component. Background Art
[0002] In the past, the following method is known: using a photosensitive composition containing a photosensitive component and a photopolymerization initiator, a conductive layer is formed on a substrate by photolithography (refer to patent documents 1 to 7). In the above method, for example, first, a photosensitive composition is applied to the substrate, dried, and formed into a film (film forming process). Then, a photomask having a predetermined opening pattern is covered on the above-mentioned formed film, and the film is exposed through the photomask (exposure process). Thus, the exposed part of the film is photocured. Then, an alkaline aqueous developer is used to corrode and remove the unexposed part that is shielded from light by the photomask (development process). Then, the film having the desired pattern is baked (baking process). According to the photolithography method including the above process, a finer conductive layer can be formed compared with various previous printing methods.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2000-199954
[0006] Patent Document 2: Japanese Patent Application Publication No. 2002-072472
[0007] Patent Document 3: Japanese Patent Application Publication No. 2006-344590
[0008] Patent Document 4: Japanese Patent Application Publication No. 2014-170051
[0009] Patent Document 5: International Publication No. 2015-151892
[0010] Patent Document 6: Japanese Patent Application Publication No. 2016-180908
[0011] Patent Document 7: Japanese Patent Application Publication No. 2016-201104 Summary of the invention
[0012] However, in recent years, the miniaturization and high performance of various electronic devices have been rapidly promoted, and the electronic components installed in the electronic devices are also required to be further miniaturized and high-densified. With this, the manufacture of electronic components requires low resistance and thinning (small size) of the conductive layer. More specifically, for example, it is required to form a thicker conductive layer to reduce resistance; improve the resolution of the pattern, and form a conductive layer with thin lines of less than 20μm / 20μm in line and space (L / S) representing the ratio of the line width of the wiring to the spacing between adjacent lines.
[0013] However, according to the research of the inventors, if the conductive layer is to be thickened or formed with the small L / S as described above, the developability is easily reduced, and it is difficult to stably form the desired pattern. For example, if the thickness of the conductive layer is increased, the curing deep near the substrate becomes insufficient, and it becomes easy for the conductive film to peel off and break during the development process. In addition, if the L / S is small, it becomes difficult to supply the developer to the space between the lines during the development process. As a result, the development time, that is, the time required until the unexposed part is completely removed (the time until the development point (BP)), becomes longer, or residues that are not fully removed sometimes remain in the space.
[0014] The present invention is made in view of the above aspects, and its purpose is to provide: a photosensitive composition with excellent developability and resolution. In addition, another related purpose is to provide: a composite having a conductive film formed from a dried body of the photosensitive composition. In addition, another related purpose is to provide: an electronic component having a conductive layer formed from a calcined body of the photosensitive composition, and a method for producing the same.
[0015] According to the present invention, a photosensitive composition is provided, which comprises: conductive powder; a cellulose-based organic binder; a (meth) acrylic photocurable resin having an acid value; a photopolymerizable compound; and a photopolymerization initiator. For the photosensitive composition, when the total of the cellulose-based organic binder, the (meth) acrylic photocurable resin having an acid value, and the photopolymerizable compound is set to 100% by mass, the content ratio of the cellulose-based organic binder is 10 to 40% by mass; the content ratio of the (meth) acrylic photocurable resin having an acid value is 5 to 40% by mass; and the content ratio of the photopolymerizable compound is 30 to 60% by mass.
[0016] In the above-mentioned photosensitive composition, three kinds of organic components, namely, a cellulose-based organic binder, a (meth) acrylic photocurable resin having an acid value, and a photopolymerizable compound are appropriately balanced. As a result, in the development process, the unexposed portion becomes easy to be removed, the development time can be shortened, and the generation of residues can be reduced. In addition, it becomes easy to cure to the depth of the exposed portion (the portion close to the substrate), the adhesion between the substrate and the exposed portion can be improved, and the generation of peeling and disconnection can be suppressed. As a result, according to the above-mentioned photosensitive composition, a conductive layer with a thin line L / S of less than 20μm / 20μm can be formed.
[0017] In a preferred embodiment disclosed herein, the cellulose-based organic binder has an acid value of 20 mgKOH / g or more. This allows the unexposed portion to be removed more quickly and cleanly in the development step.
[0018] In a preferred embodiment disclosed herein, the acid value of the (meth) acrylic photocurable resin having an acid value is 50 mgKOH / g or more and 150 mgKOH / g or less. As a result, the removability of the unexposed portion and the etching resistance of the exposed portion can be balanced at a higher level. That is, in the development process, the unexposed portion can be removed more quickly and cleanly, and the peeling and disconnection of the exposed portion can be better suppressed.
[0019] In a preferred embodiment disclosed herein, the weight average molecular weight of the (meth)acrylic photocurable resin having an acid value is 10,000 to 30,000. Thus, even with a small exposure amount, the exposed portion can be cured appropriately to a deep depth.
[0020] In a preferred embodiment disclosed herein, when the total of the cellulose-based organic binder, the (meth) acrylic photocurable resin having an acid value, and the photopolymerizable compound is set to 100% by mass, the content ratio of the cellulose-based organic binder is 20 to 35% by mass; the content ratio of the (meth) acrylic photocurable resin having an acid value is 10 to 30% by mass; and the content ratio of the photopolymerizable compound is 50 to 60% by mass. Thus, the developability and / or resolution can be further improved, and the technical effect disclosed herein can be exerted at a higher level.
[0021] In a preferred embodiment disclosed herein, the conductive powder contains silver-based particles, thereby achieving a conductive layer having an excellent balance between cost and low resistance.
[0022] According to the present invention, there is provided a composite body comprising: a green sheet; and a conductive film which is disposed on the green sheet and is formed from a dried product of the photosensitive composition.
[0023] In addition, according to the present invention, there is provided an electronic component comprising: a conductive layer formed from a calcined body of the above-mentioned photosensitive composition. According to the above-mentioned photosensitive composition, a conductive layer of thin lines with a small L / S can be formed with good reproducibility. Therefore, by using the above-mentioned photosensitive composition, an electronic component having a small and / or high-density conductive layer can be suitably realized.
[0024] In addition, according to the present invention, there is provided a method for manufacturing an electronic component, which comprises the following steps: applying the above-mentioned photosensitive composition to a substrate, exposing and developing, and then baking to form a conductive layer formed by a baked body of the above-mentioned photosensitive composition. By such a manufacturing method, electronic components with small and / or high-density conductive layers can be stably manufactured, and productivity and yield can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional view schematically showing the structure of a multilayer chip inductor according to one embodiment of the present invention.
[0026] Figure 2 Optical microscope image of the wiring pattern of Example 1.
[0027] Description of Reference Numerals
[0028] 1 Multilayer Chip Inductor
[0029] 10 Main body
[0030] 12 Ceramic layer
[0031] 14 Internal electrode layer
[0032] 20 External electrodes DETAILED DESCRIPTION
[0033] The following is a description of suitable embodiments of the present invention. It should be noted that matters necessary for implementing the present invention (such as a method for preparing a photosensitive composition, a conductive film, a method for forming a conductive layer, a method for manufacturing an electronic component, etc.) other than matters specifically mentioned in this specification (such as the composition of the photosensitive composition) can be understood based on the technical content taught in this specification and the general technical knowledge of those skilled in the art in this field. The present invention can be implemented based on the contents disclosed in this specification and the technical knowledge in this field.
[0034] It should be noted that, in the following description, a film-like body (dried product) obtained by drying a photosensitive composition at a temperature below the boiling point of an organic component, specifically, at approximately 200°C or below, for example, at 100°C or below, is referred to as a "conductive film". The conductive film includes all unfired (before firing) film-like bodies. The conductive film may be an uncured material before photocuring, or a cured material after photocuring. In addition, in the following description, a sintered body (fired product) obtained by firing a photosensitive composition at a temperature above the sintering temperature of a conductive powder is referred to as a "conductive layer". The conductive layer includes wiring (linear body), wiring pattern, and solid pattern.
[0035] In addition, the expression "A to B" which shows a range in this specification means A or more and B or less.
[0036] 《Photosensitive composition》
[0037] The photosensitive composition disclosed herein can be suitably used for, for example, the preparation of a conductive layer of wiring including fine wires having an L / S of 20 μm / 20 μm or less, particularly ultrafine wires having an L / S of 15 μm / 15 μm or less. The photosensitive composition disclosed herein contains (A) conductive powder, (B) organic binder, (C) photocurable resin, (D) photopolymerizable compound, and (E) photopolymerization initiator as essential components. The components are described in order below.
[0038] <(A) Conductive powder>
[0039] Conductive powder is a component that imparts conductivity to the conductive layer obtained by, for example, baking the photosensitive composition. As conductive powder, it is not particularly limited, for example, it can be used alone or in combination of two or more kinds from the previously known materials according to the purpose, etc. Suitable examples of conductive powder include simple substances of metals such as gold (Au), silver (Ag), copper (Cu), platinum (Pt), palladium (Pd), aluminum (Al), nickel (Ni), ruthenium (Ru), rhodium (Rh), tungsten (W), iridium (Ir), osmium (Os), and their mixtures, alloys, etc. As alloys, for example, silver alloys such as silver-palladium (Ag-Pd), silver-platinum (Ag-Pt), and silver-copper (Ag-Cu) can be cited.
[0040] In a suitable embodiment, the conductive powder includes silver particles. Silver has a low cost and high conductivity. Therefore, by including silver particles, the conductive powder can achieve a conductive layer with an excellent balance between cost and low resistance.
[0041] It should be noted that in this specification, "silver-based particles" include all substances containing silver components. Examples of silver-based particles include single substance silver, the above-mentioned silver alloys, core-shell particles with silver-based particles as cores, such as silver-ceramic core-shell particles, etc.
[0042] Although not particularly limited, the D of the conductive powder is 50 The particle size (equivalent to the particle size at which the cumulative value from the smaller particle size side in the volume-based particle size distribution based on the laser diffraction / scattering method is 50%) is preferably about 0.1 to 5 μm. 50 The particle size is within the above range, so that the exposure performance of the exposed part can be improved, and thin lines can be formed more stably. From the viewpoint of suppressing aggregation in the photosensitive composition and improving stability, the D of the conductive powder is preferably 50 The particle size may be, for example, 0.5 μm or more, or 1 μm or more. In addition, from the viewpoint of improving the fine line formation property or promoting the densification and low resistance of the conductive layer, the D of the conductive powder may be 50 The particle size may be, for example, 4.5 μm or less or 4 μm or less.
[0043] The conductive powder may have an organic surface treatment agent attached to its surface. The organic surface treatment agent may be used for at least one of the following purposes, for example, to improve the dispersibility of the conductive powder in the photosensitive composition, to improve the affinity of the conductive powder with other components contained, and to prevent surface oxidation of the metal constituting the conductive powder. Examples of the organic surface treatment agent include fatty acids such as carboxylic acids, and benzotriazole compounds.
[0044] Although not particularly limited, the proportion of the conductive powder in the photosensitive composition as a whole is about 50% by mass or more, typically 60 to 95% by mass, preferably 70 to 90% by mass. By satisfying the above range, it is suitable for forming a conductive layer with excellent compactness and conductivity. In addition, the operability of the photosensitive composition and the workability when formed into a conductive film can be improved.
[0045] <(B) Organic binder>
[0046] The organic binder is a component for improving the adhesion between the substrate and the conductive film (uncured material) before photocuring. In addition, there is the following contradiction: the development time of the photosensitive composition containing the (C) photocurable resin described later as an essential component becomes longer. Therefore, in the technology disclosed herein, the organic binder is a component for compensating for the above contradiction and shortening the development time or improving the developability. The organic binder is different from the (C) photocurable resin and the (D) photopolymerizable compound described later, and it does not have photosensitivity (e.g., photocurability). In this embodiment, the organic binder is composed of a cellulose compound. By including a cellulose compound, the (A) conductive powder is easily compatible with the (C) photocurable resin and the (D) photopolymerizable compound described later, and the storage stability of the photosensitive composition can be improved. In addition, the cellulose compound typically has multiple hydroxyl groups in the repeating structural unit of cellulose, i.e., the glucose ring, and exhibits good water solubility. Therefore, it can be easily removed with an aqueous developer in the development process.
[0047] Cellulose compounds include cellulose, cellulose derivatives, and salts thereof. As cellulose compounds, one kind can be used alone or two or more kinds can be used in combination from conventionally known substances. Suitable examples of cellulose compounds include hydroxyalkyl celluloses such as hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose; alkyl celluloses such as methyl cellulose and ethyl cellulose; carboxyalkyl celluloses such as carboxymethyl cellulose; and the like.
[0048] When an alkaline aqueous developer is used in the development process, it is preferred that the cellulose compound has a highly alkali-soluble structural portion, such as an acidic group such as a phenolic hydroxyl group, a carboxyl group, a sulfonic group, a phosphonyl group, or a boric acid group. Among them, a carboxyl group is preferred. The acidic group is a substituent having a dissociable proton and showing acidity in water. A portion of the acidic group may be esterified. The acidic group may be bonded to a carbon atom of the main chain (the carbon chain with the largest number of carbon atoms, the same below) of the cellulose compound, or may be bonded to a carbon atom of a side chain (the carbon chain branching from the main chain, the same below). By including a highly alkali-soluble structural portion, it is easier to remove the unexposed portion more quickly and without residue using an alkaline aqueous developer.
[0049] In a suitable embodiment, the cellulose compound has an acid value. The acid value of the cellulose compound is about 10 mgKOH / g or more, preferably 20 mgKOH / g or more, more preferably 25 mgKOH / g or more, for example, 30 mgKOH / g or more, typically less than the (meth) acrylic photocurable resin described later, about 150 mgKOH / g or less, preferably 100 mgKOH / g or less, for example, 50 mgKOH / g or less is preferred. More preferably, the acid value of the organic binder as a whole is within the above range. In other words, it is preferred that the organic binder as a whole shows a specified acidity. If the acid value is above the specified value, the removability of the unexposed part in the development process can be improved, and the developability can be better improved. In addition, if the acid value is below the specified value, the solubility in the aqueous developer is suppressed, and the peeling and disconnection of the exposed part in the development process can be better suppressed. Therefore, the technical effects disclosed herein can be exerted at a higher level.
[0050] In addition, the "acid value" in this specification refers to the content (mg) of potassium hydroxide (KOH) required to neutralize the free fatty acids contained in a unit sample (1g). The unit is mgKOH / g.
[0051] In a suitable embodiment, the cellulose compound includes a cellulose polymer compound having a weight average molecular weight of 5000 or more. By including the cellulose polymer compound, the adhesion (stickiness) of the conductive film to the substrate before photocuring is improved, which can be suitable for suppressing undesirable conditions such as peeling and disconnection in the conductive layer. The cellulose polymer compound may contain an acidic group in the repeating structural unit. In addition, the weight average molecular weight of the cellulose polymer compound is preferably higher than the (meth) acrylic photocurable resin described later. For example, it is preferably about 2 times or more, for example, 3 times or more, higher than the weight average molecular weight of the (meth) acrylic photocurable resin. The weight average molecular weight of the cellulose polymer compound can be about 10,000 or more, typically 20,000 or more, for example, 50,000 or more, and about 1 million or less, typically 500,000 or less, for example, 200,000 or less.
[0052] In addition, the "weight average molecular weight" in this specification means the weight-based average molecular weight obtained by measuring by gel permeation chromatography (GPC) and converting using a standard polystyrene calibration curve.
[0053] The organic binder can be composed only of the above-mentioned cellulose compound, and other compounds currently known to be used in this application can be included on the basis of the cellulose compound without significantly reducing the technical effect disclosed herein. As such compounds, for example, acrylic resins, phenolic resins, epoxy resins, polyester resins, polyamide resins, polycarbonate resins, etc. can be cited. The ratio of the cellulose compound to the organic binder as a whole is about 50% by mass or more, typically 80% by mass or more, for example, preferably 90% by mass or more, and can also be substantially 100% by mass (95% by mass or more).
[0054] Although not particularly limited, the ratio of the organic binder in the photosensitive composition as a whole is typically lower than that of the (D) photopolymerizable compound described later, and is about 0.1 to 20% by mass, typically 0.5 to 10% by mass, for example, 1 to 5% by mass is preferred. By making the ratio of the organic binder above the specified value, the developability can be improved in the development process and the development time can be shortened. In addition, the retention (etching resistance) of the photosensitive composition on the substrate can be improved, and peeling and disconnection of the exposed part can be better suppressed. By making the ratio of the organic binder below the specified value, the ratio of the photosensitive component, that is, the ratio of the (C) photocurable resin and the (D) photopolymerizable compound described later, is relatively increased, and the conductive film before photocuring can be cured more stably in the exposure process.
[0055] <(C) Photocurable resin>
[0056] Photocurable resin is a photocurable component that produces polymerization reaction, crosslinking reaction, etc. and cures by light irradiation. Compared with the (D) photopolymerizable compound described later, the photocurable resin can be cured with a small amount of exposure. Therefore, in the technology disclosed herein, the photocurable resin is a photocurable component used to solidly cure to the depth of the exposed part (the part close to the substrate). The polymerization reaction can be, for example, addition polymerization or ring-opening polymerization. In this specification, the photocurable resin does not include monomers, and it includes polymers and oligomers (prepolymers). The photocurable resin typically has one or more unsaturated bonds and / or cyclic structures. The unsaturated bonds and / or cyclic structures can be bonded to carbon atoms in the main chain of the photocurable resin, or to carbon atoms in the side chain.
[0057] In this embodiment, the photocurable resin includes: a (meth) acrylic photocurable resin (hereinafter also referred to as a (meth) acrylic resin) having a monomer having a (meth) acryloyl group as a structural unit. By including the (meth) acrylic resin, the flexibility of the conductive layer and the followability to the substrate can be improved, and the occurrence of peeling and disconnection can be better suppressed. In addition, the durability of the conductive layer can be improved.
[0058] It should be noted that in this specification, "(meth)acryloyl" is a term including "methacryloyl (-C(=O)-C(CH3)=CH2)" and "acryloyl (-C(=O)-CH=CH2)", and "(meth)acrylate" is a term including "methacrylate" and "acrylate".
[0059] As the (meth)acrylic resin, one kind can be used alone or two or more kinds can be used in combination from the conventionally known materials. As a suitable example of the (meth)acrylic resin, there can be mentioned: a homopolymer of an alkyl (meth)acrylate; a copolymer having an alkyl (meth)acrylate as a main monomer and containing a secondary monomer copolymerizable with the main monomer. Among them, from the viewpoint of improving the photocurability, a (meth)acrylic resin having a (meth)acryloyl group (preferably an acryloyl group) on the side chain is preferred.
[0060] Specific examples of homopolymers include polymethyl (meth) acrylate, polyethyl (meth) acrylate, polybutyl (meth) acrylate, etc. Specific examples of copolymers include block copolymers containing polymers of methacrylate and polymer blocks of acrylate as repeating structural units. Specific examples of methacrylates include methyl methacrylate, propyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, etc. Specific examples of acrylates include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, tert-butyl acrylate, n-hexyl acrylate, etc.
[0061] In this embodiment, the (meth) acrylic resin includes: a monomer unit derived from an acidic group-containing monomer having an acidic group. For example, it includes: a monomer unit further containing at least one of a phenolic hydroxyl group, a carboxyl group, a sulfonic group, a phosphonyl group, and a boric acid group on the basis of a (meth) acryloyl group. As a result, the removability of the uncured portion in the development process can be effectively improved, the developability can be improved, and the development time can be shortened. The acidic group can be bonded to a carbon atom of the main chain or to a carbon atom of the side chain.
[0062] Specific examples of (meth)acrylic resins include, for example, carboxyl-containing (meth)acrylic resins, phosphonyl-containing (meth)acrylic resins, acid-modified epoxy (meth)acrylic resins, carboxyl-containing urethane-modified epoxy (meth)acrylic resins, etc. Among them, preferably included are (meth)acrylic resins containing (meth)acryloyl groups and carboxyl groups. Commercially available products of (meth)acrylic resins having an acidic group include, for example, CYCLOMER P (trademark) ACA Z200M, Z230AA, Z250, Z251, Z300, Z320, Z254F, etc. manufactured by DaicelOrnex Co., Ltd.
[0063] In the present embodiment, the (meth) acrylic resin has an acid value. The resin acid value of the (meth) acrylic resin is about 30 mgKOH / g or more, typically 40 mgKOH / g or more, preferably 50 mgKOH / g or more, for example 60 mgKOH / g or more, and about 300 mgKOH / g or less, typically 200 mgKOH / g or less, preferably 150 mgKOH / g or less, for example 135 mgKOH / g or less is preferred. More preferably, the resin acid value of the photocurable resin as a whole is within the above range. In other words, it is preferred that the photocurable resin as a whole shows a specified acidity. If the resin acid value is above the specified value, the unexposed portion can be removed more quickly and cleanly in the development process. In addition, if the resin acid value is below the specified value, the solubility in the aqueous developer is suppressed, and the peeling and disconnection of the exposed portion in the development process can be better suppressed.
[0064] In a suitable embodiment, the photocurable resin contains a polymer with a weight average molecular weight of 5000 or more. When the photocurable resin contains a polymer, the adhesion to the substrate is improved, and the following situations are likely to occur: the development time in the development process becomes longer, or the developability decreases. Therefore, the application of the technology disclosed herein is effective. The weight average molecular weight of the photocurable resin is usually greater than the photopolymerizable compound described later, and preferably less than the weight average molecular weight of the above-mentioned cellulose-based organic binder. Specifically, it is about 7000 or more, preferably 10,000 or more, for example, 14,000 or more, and about 100,000 or less, typically 50,000 or less, preferably 30,000 or less. Thus, the exposed part can be suitably cured even to a deep depth with a small exposure amount.
[0065] In a suitable embodiment, the double bond equivalent of the (meth)acrylic resin (calculated value as weight average molecular weight / number of C=C double bonds) is about 200 or more, typically 300 or more, further 350 or more, for example 380 or more, and about 1500 or less, typically 1200 or less, for example 1100 or less. If the double bond equivalent is within the above range, the removability of the unexposed portion and the etching resistance of the exposed portion can be balanced at a high level in the development process. That is, the development time can be shortened more effectively, and the occurrence of peeling and disconnection can be suppressed more effectively.
[0066] In a suitable embodiment, the glass transition point (Tg value based on differential scanning calorimetry (DSC)) of the (meth) acrylic resin is about 40°C or above, typically 50°C or above, for example 60°C or above, further 100°C or above, in one example 120°C or above, 130°C or above, and about 200°C or below, for example 150°C or below. As a result, the flexibility and adhesion of the exposed portion can be better improved, and the occurrence of peeling and disconnection can be better suppressed. In addition, when the Tg value is within the above range, the adhesion of the conductive film to the substrate before photocuring is improved, and the removability of the unexposed portion in the development process is reduced. Therefore, the application of the technology disclosed herein is effective.
[0067] The photocurable resin may be composed of the above-mentioned (meth) acrylic resin alone, or may contain other resins known to be used in this application in addition to the (meth) acrylic resin, within the range that the technical effects disclosed herein are not significantly reduced. The ratio of the (meth) acrylic resin to the entire photocurable resin is about 50% by mass or more, typically 80% by mass or more, preferably 90% by mass or more, and may be substantially 100% by mass (95% by mass or more).
[0068] Although not particularly limited, the ratio of the photocurable resin in the photosensitive composition as a whole is typically lower than that of the (D) photopolymerizable compound described later, and is about 0.1 to 50% by mass, typically 0.5 to 30% by mass, for example 1 to 20% by mass, and preferably 2 to 10% by mass. By making the ratio of the photocurable resin above the specified value, the exposed part can be cured with good precision to the depth, and the peeling and disconnection of the exposed part can be better suppressed. By making the ratio of the photocurable resin below the specified value, the ratio of the (B) organic binder and the (D) photopolymerizable compound described later is relatively increased, the developability can be better improved, and the development time can be further shortened.
[0069] Although not particularly limited, when the total amount of the polymer components, that is, the total amount of the (B) organic binder and the (C) photocurable resin ((B) + (C)) is set to 100% by mass, the content ratio of the (C) photocurable resin is about 5% by mass or more, preferably 10% by mass or more, more preferably 20% by mass or more, and about 90% by mass or less, preferably 70% by mass or less, and more preferably 65% by mass or less. Thus, the effect of improving the developability by using the organic binder and the effect of preventing the peeling by using the photocurable resin can be stably exerted at a higher level.
[0070] <(D) Photopolymerizable compound>
[0071] Photopolymerizable compounds are photocurable components that utilize active species generated during the decomposition of the photopolymerization initiator (E) described later to generate polymerization reactions, crosslinking reactions, etc. and cure. In addition, in the technology disclosed herein, photopolymerizable compounds are photocurable components used to complete curing within a short development time. Photopolymerizable compounds are monomers having one or more polymerizable functional groups. Photopolymerizable compounds include: monofunctional monomers having one polymerizable functional group per molecule; polyfunctional monomers having two or more polymerizable functional groups per molecule; and modified products thereof. Photopolymerizable compounds typically have one or more unsaturated bonds and / or cyclic structures. As a suitable example of a photopolymerizable compound, there can be cited free radical polymerizable monomers having one or more unsaturated bonds such as (meth)acryloyl groups and vinyl groups, and cationic polymerizable monomers having a cyclic structure such as an epoxy group.
[0072] In a suitable scheme, the photopolymerizable compound includes a (meth) acrylate monomer with a (meth) acryloyl group. Thus, the affinity with the photocurable resin of (meth) acrylic acid can be improved, and the storage stability of the photosensitive composition can be improved. As a suitable example of a (meth) acrylate monomer, triethylene glycol monoacrylate, triethylene glycol monomethacrylate, tetraethylene glycol monoacrylate, tetraethylene glycol monomethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, tripentaerythritol heptaacrylate, tripentaerythritol octaacrylate, four-season pentaerythritol nine acrylate, four-season pentaerythritol ten acrylate, etc. can be cited. Wherein, from the viewpoint of improving photocurability, it is preferred that there are more than 3 (meth) acryloyl groups in each molecule, and then there are more than 5 (meth) acryloyl monomers.
[0073] In another suitable embodiment, the photopolymerizable compound includes a carbamate bond-containing compound having a carbamate bond (-NH-C(=O)-O-). By including the carbamate bond-containing compound, the etching resistance of the exposed portion can be better improved, and a conductive layer with better flexibility and stretchability can be achieved. Therefore, the adhesion between the substrate and the conductive layer can be improved, and the occurrence of peeling and disconnection can be suppressed at a high level. As a suitable example of a carbamate bond-containing compound, carbamate-modified (meth)acrylates and carbamate-modified epoxies containing carbamate bonds in the above-mentioned (meth)acrylate monomers can be cited.
[0074] Although not particularly limited, the weight average molecular weight of the photopolymerizable compound is usually smaller than that of the above-mentioned cellulose-based organic binder and (meth)acrylic photocurable resin, and is about 2000 or less, typically 100 to 1500, and preferably 500 to 1300.
[0075] Although not particularly limited, the ratio of the photopolymerizable compound in the photosensitive composition as a whole is typically higher than that of (B) the organic binder and (C) the photocurable resin, and is about 0.1 to 50% by mass, typically 0.5 to 30% by mass, for example 1 to 20% by mass, and preferably 2 to 10% by mass. By making the ratio of the photopolymerizable compound above the specified value, the developability can be improved and the development time can be further shortened. By making the ratio of the photopolymerizable compound below the specified value, the ratio of the polymer components, that is, the ratio of (B) the organic binder and (C) the photocurable resin, is relatively increased, and the retention of the photosensitive composition on the substrate can be improved. As a result, peeling and disconnection of the exposed part can be better suppressed.
[0076] Although not particularly limited, when the total amount of the photosensitive components, i.e., the total amount of the (C) photocurable resin and the (D) photopolymerizable compound ((C) + (D)) is set to 100% by mass, it is preferred that the content of the (D) photopolymerizable compound is greater than that of the (C) photocurable resin. Specifically, the content of the (D) photopolymerizable compound is more than 50% by mass, preferably 55% by mass or more, more preferably 60% by mass or more, and is preferably about 95% by mass or less, preferably 90% by mass or less, and more preferably 85% by mass or less. Thus, the effect of preventing peeling by using the photocurable resin and the effect of shortening the development time by using the photopolymerizable compound can be stably exerted at a higher level.
[0077] <(E) Photopolymerization initiator>
[0078] Photopolymerization initiator is a component that decomposes by irradiation with light energy such as ultraviolet rays, generates active species such as free radicals and cations, and thus initiates the polymerization reaction of photopolymerizable compounds. As a photopolymerization initiator, one kind can be used alone or two or more kinds can be used in suitable combination according to the type of photosensitive resin. As a suitable example, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4-diethylthioxanthone, benzophenone, etc. can be cited.
[0079] Although not particularly limited, the ratio of the photopolymerization initiator to the entire photosensitive composition is about 0.01 to 5 mass %, typically 0.1 to 3 mass %, for example 0.2 to 2 mass %, preferably. This allows the photocurability of the photosensitive composition to be fully utilized, and allows a more stable formation of the conductive layer.
[0080] <(F) Organic dispersion medium>
[0081] The photosensitive composition may contain an organic dispersion medium for dispersing these components in addition to the above-mentioned essential components. The organic dispersion medium is a component that imparts appropriate viscosity and fluidity to the photosensitive composition, improves the operability of the photosensitive composition, or improves the operability when it is formed into a conductive film. As the organic dispersion medium, one kind can be used alone or two or more kinds can be used in combination, for example, according to the type of the photopolymerizable compound.
[0082] As a suitable example of an organic dispersion medium, there can be mentioned alcohol solvents such as pineol, dihydropineol (menthol), TEXANOL, 3-methyl-3-methoxybutanol, and benzyl alcohol; glycol solvents such as ethylene glycol, propylene glycol, and diethylene glycol; ether solvents such as dipropylene glycol methyl ether, methyl cellosolve (ethylene glycol monomethyl ether), cellosolve (ethylene glycol monoethyl ether), and butyl carbitol (diethylene glycol monobutyl ether); ester solvents such as diethylene glycol monobutyl ether acetate, dipropylene glycol methyl ether acetate, butanediol acetate, butyl diglycol acetate, butyl cellosolve acetate, butyl carbitol acetate (diethylene glycol monobutyl ether acetate), and isobornyl acetate; hydrocarbon solvents such as toluene, xylene, naphtha, and petroleum hydrocarbons; mineral spirits; and other organic solvents.
[0083] Among them, from the viewpoint of improving the storage stability of the photosensitive composition and the workability during the formation of the conductive film, an organic solvent having a boiling point of 150° C. or higher, and more preferably an organic solvent having a boiling point of 170° C. or higher is preferred. In addition, as another suitable example, from the viewpoint of suppressing the drying temperature after printing the conductive film to a low level, an organic solvent having a boiling point of 250° C. or lower, and more preferably an organic solvent having a boiling point of 220° C. or lower is preferred. This can improve productivity and reduce production costs.
[0084] Suitable commercially available organic solvents include, for example, Dawanor DPM (trademark) (boiling point: 190° C., manufactured by Dow Chemical Company), Dawanor DPMA (trademark) (boiling point: 209° C., manufactured by Dow Chemical Company), menthol (boiling point: 207° C.), menthol P (boiling point: 216° C.), Isopar H (boiling point: 176° C., manufactured by Kanto Fuel Co., Ltd.), and SW-1800 (boiling point: 198° C., manufactured by Maruzen Oil Co., Ltd.).
[0085] When the photosensitive composition contains an organic dispersion medium, there is no particular limitation, and the ratio of the organic dispersion medium to the entire photosensitive composition may be about 1 to 50 mass %, typically 3 to 30 mass %, for example 5 to 20 mass %.
[0086] <(G) Other added ingredients>
[0087] Photosensitive composition can further contain various additives as required on the basis of the above-mentioned components as long as it does not obviously damage the effect of the technology disclosed herein. As additives, one kind can be used alone or two or more kinds can be used in suitable combination from the previously known substances. As an example of additives, for example, inorganic fillers, photosensitizers, inhibitors, free radical scavengers, antioxidants, ultraviolet absorbers, plasticizers, surfactants, leveling agents, thickeners, dispersants, defoamers, anti-gelling agents, stabilizers, preservatives, pigments, etc. can be cited. Although not particularly limited, the ratio of additives in the overall photosensitive composition is about 5% by mass or less, typically 3% by mass or less, for example 2% by mass or less, preferably 1% by mass or less.
[0088] The three organic components of the photosensitive composition disclosed herein are appropriately balanced. That is, when the total of the cellulose-based organic binder, the (meth) acrylic photocurable resin, and the photopolymerizable compound is set to 100% by mass, the content ratio of the cellulose-based organic binder is 10 to 40% by mass (preferably 20 to 35% by mass); the content ratio of the (meth) acrylic photocurable resin is 5 to 40% by mass (preferably 10 to 30% by mass); and the content ratio of the photopolymerizable compound is 30 to 60% by mass (preferably 50 to 60% by mass). As a result, the unexposed part becomes easy to be removed in the development process, the development time can be shortened, and the occurrence of residues can be reduced. In addition, it becomes easy to cure to the depth of the exposed part, the adhesion between the substrate and the exposed part can be improved, and the occurrence of peeling and disconnection can be suppressed. Therefore, it can also be suitable for forming a conductive layer of a fine line with an L / S of 20μm / 20μm or less, and further a conductive layer of an ultrafine line with an L / S of 15μm / 15μm or less. In addition, a thick conductive layer having a thickness of 5 μm or more, or even 10 μm or more, can be suitably formed. As a result, productivity and yield can be improved.
[0089] 《Application of photosensitive composition》
[0090] According to the photosensitive composition disclosed herein, a conductive layer of a thin line can be stably formed. Therefore, the photosensitive composition disclosed herein can be suitably used for forming a conductive layer in various electronic components such as inductor components, capacitor components, and multilayer circuit boards.
[0091] The electronic components can be variously mounted in various forms such as surface mount type and through-hole mount type. The electronic components can be stacked type, winding type, or thin film type. Typical examples of inductor components include high-frequency filters, common mode filters, inductors (coils) for high-frequency circuits, inductors (coils) for general circuits, high-frequency filters, choke coils, transformers, etc.
[0092] As an example of electronic components, ceramic electronic components can be cited. It should be noted that in this specification, "ceramic electronic components" refer to all electronic components made of ceramic materials, including all electronic components with amorphous ceramic substrates (glass ceramic substrates) or crystalline (i.e. non-glass) ceramic substrates. Typical examples of ceramic electronic components include: high-frequency filters with ceramic substrates, ceramic inductors (coils), ceramic capacitors, low-temperature co-fired ceramic substrates (LTCC substrates), high-temperature co-fired ceramic substrates (HTCC substrates), etc.
[0093] In addition, there are no special restrictions on the ceramic material, and examples include oxide materials such as zirconium oxide (zirconia), magnesium oxide (magnesium oxide), aluminum oxide (aluminum oxide), silicon oxide (silicon dioxide), titanium oxide (titania), cerium oxide (cerium oxide), yttrium oxide (yttrium oxide), and barium titanate; composite oxide materials such as cordierite, mullite, forsterite, talc, sialon, zircon, and ferrite; nitride materials such as silicon nitride (silicon nitride) and aluminum nitride (aluminum nitride); carbide materials such as silicon carbide (silicon carbide); hydroxide materials such as hydroxyapatite; and the like.
[0094] Figure 1 1 is a cross-sectional view schematically showing the structure of the multilayer chip inductor 1. It should be noted that: Figure 1 The dimensional relationships (length, width, thickness, etc.) in the drawings do not necessarily reflect the actual dimensional relationships. In addition, the symbols X and Y in the drawings represent the left-right direction and the up-down direction, respectively. However, these are only directions for convenience of explanation.
[0095] The multilayer chip inductor 1 includes a main body 10 and external electrodes 20 provided on both side surfaces of the main body 10 in the left-right direction X. The multilayer chip inductor 1 has a size such as 1608 shape (1.6 mm×0.8 mm) or 2520 shape (2.5 mm×2.0 mm).
[0096] The main body 10 has a structure in which a ceramic layer (dielectric layer) 12 and an internal electrode layer 14 are integrated. The ceramic layer 12 is made of a ceramic material. In the vertical direction Y, the internal electrode layer 14 is arranged between the ceramic layers 12. The internal electrode layer 14 is formed using the above-mentioned photosensitive composition. The internal electrode layers 14 adjacent to each other in the vertical direction Y sandwiching the ceramic layer 12 are connected by means of a through hole 16 provided in the ceramic layer 12. As a result, the internal electrode layer 14 is configured into a three-dimensional spiral shape (spiral shape). Both ends of the internal electrode layer 14 are connected to the external electrodes 20 respectively.
[0097] Such a multilayer chip inductor 1 can be manufactured, for example, by the following steps.
[0098] That is, first, a paste containing a ceramic material as a raw material, a binder resin and an organic solvent is prepared, and the paste is supplied to a carrier sheet to form a ceramic green sheet. Next, the ceramic green sheet is rolled and cut into a desired size to obtain a plurality of green sheets for forming a ceramic layer. Next, via holes are appropriately formed at predetermined positions of the plurality of green sheets for forming a ceramic layer using a puncher or the like.
[0099] Next, the photosensitive composition is used to form a conductive film of a predetermined coil pattern at predetermined positions of a plurality of raw sheets for forming a ceramic layer. As an example, a conductive film in an unfired state can be formed by a manufacturing method including the following steps: (Step S1: Film-forming step) a step of applying a photosensitive composition to a raw sheet for forming a ceramic layer and drying it to form a conductive film formed of a dried body of the photosensitive composition; (Step S2: Exposure step) a step of covering the conductive film with a photomask having a predetermined opening pattern, exposing the conductive film through the photomask, and partially photocuring the conductive film; (Step S3: Development step) a step of etching the photocured conductive film to remove the unexposed portion.
[0100] It should be noted that when the above-mentioned photosensitive composition is used to form a conductive film, a conventionally known method can be appropriately used. For example, in (step S1), the photosensitive composition can be applied using various printing methods such as screen printing, a rod coater, etc. The photosensitive composition can be dried at a temperature below the boiling point of the photopolymerizable compound and the photopolymerization initiator, typically at 50 to 100°C. In (step S2), exposure can be performed using, for example, an exposure machine that emits light in a wavelength range of 10 to 500nm, such as a high-pressure mercury lamp, a metal halide lamp, a xenon lamp, and other ultraviolet irradiation lamps. In (step S3), etching can typically use an alkaline aqueous developer. For example, an aqueous solution containing sodium hydroxide, sodium carbonate, etc. can be used. The concentration of the alkaline aqueous solution can be adjusted to, for example, 0.01 to 0.5% by mass.
[0101] Next, (step S4: firing process) a plurality of green sheets for forming a ceramic layer having an unfired conductive film are stacked and pressed together. Thus, a stack of unfired ceramic green sheets is produced. Next, the stack of ceramic green sheets is fired, for example, at 600 to 1000° C. Thus, the ceramic green sheets are sintered into one body to form a main body 10, which includes: a ceramic layer 12; and an internal electrode layer 14 formed by a fired body of a photosensitive composition. Then, an appropriate external electrode forming paste is applied to both ends of the main body 10 and fired, thereby forming an external electrode 20.
[0102] As described above, the multilayer chip inductor 1 can be manufactured.
[0103] Several embodiments of the present invention will be described below, but the present invention is not intended to be limited to the contents shown in these embodiments.
[0104] (Preparation of Photosensitive Composition)
[0105] First, prepare silver powder (D 50Particle size: 2 μm) as conductive powder. In addition, a cellulose-based polymer compound (resin acid value: 30 mgKOH / g, weight average molecular weight: 90,000, double bond equivalent: 0) is prepared as an organic binder. In addition, a urethane acrylate monomer is prepared as a photopolymerizable compound. In addition, IRGACURE (trademark) 369 manufactured by BASF Japan Ltd. is prepared as a photopolymerization initiator. In addition, four types of acrylic resins a to d shown in the following Table 1 are prepared as photocurable resins. It should be noted that the case where "ND" is shown in the resin acid value column of Table 1 means that it is below the detection limit (not detected).
[0106] [Table 1]
[0107] Table 1
[0108]
[0109] Then, the prepared silver powder, cellulose polymer compound, acrylic resins a to d, photopolymerizable compound and photopolymerization initiator, and other additive components (here, photosensitizer, anti-gelling agent, polymerization inhibitor and ultraviolet absorber) are dissolved in an organic dispersion medium to prepare a photosensitive composition (Examples 1 to 8, Comparative Examples 1 to 4). At this time, the cellulose polymer compound, acrylic resins a to d and photopolymerizable compound are blended so as to have the content ratio shown in Table 2. It should be noted that the mass ratio shown in Table 2 is the content ratio (mass %) of each component when the total of the cellulose polymer compound, acrylic resins a to d and photopolymerizable compound is set to 100 mass %.
[0110] (Wiring pattern production)
[0111] First, the prepared photosensitive composition was applied onto commercially available ceramic green sheets in a size of 4 cm x 4 cm by screen printing, and then dried at 60°C for 15 minutes to form a conductive film (solid film) on the green sheet (film-like body forming step).
[0112] Next, a photomask was placed over the conductive film. At this time, a photomask having a pattern in which the ratio (L / S) between the line width of the wiring and the spacing between adjacent lines was 20 μm / 20 μm was used as the photomask. With the photomask placed over the conductive film, an exposure machine was used to expose the conductive film at an illumination of 9 mJ / cm 2 、Exposure 1800mJ / cm 2 The exposed portion is irradiated with light under the conditions to cure the exposed portion (exposure step).
[0113] After exposure, a 0.1 mass % alkaline Na2CO3 aqueous solution (developer) is blown onto the surface of the ceramic green sheet until the break point (BP) is reached (development process). It should be noted that BP is the time until the unexposed portion is developed in a 0.1 mass % alkaline developer and the unexposed portion disappears as can be visually confirmed.
[0114] After removing the unexposed portion, the film was washed with pure water and dried at room temperature. Thus, a conductive film (dried film) having a wiring pattern of L / S=20 μm / 20 μm was formed on the ceramic green sheet.
[0115] (Evaluation of Development Property)
[0116] The developability of the wiring patterns prepared as described above was evaluated.
[0117] That is, the time (development time) until the development point (BP) is reached in the above-mentioned development process is measured. The results are shown in the "Development Time (Seconds)" column of Table 2. In addition, based on the results, the developability is evaluated with the following indices. The results are shown in the "Evaluation of Developability" column of Table 2.
[0118] “⊚”: The developing time is within 45 seconds (developing property is particularly good).
[0119] “◯”: The developing time is within 60 seconds (developability is good).
[0120] "X": The developing time is longer than 60 seconds (poor developing property).
[0121] (Resolution Evaluation)
[0122] In the exposure process, a photomask having a pattern of L / S of 15 μm / 15 μm, 20 μm / 20 μm, 25 μm / 25 μm, 30 μm / 30 μm, or 40 μm / 40 μm is used as a photomask. In addition, in the development process, the development time is set to 1.4 times the development point (BP) in consideration of the development process margin. In addition, a conductive film (dry film) having a wiring pattern of a predetermined L / S is formed in the same manner as the formation of the wiring pattern.
[0123] Next, a total of 10 fields of view were observed for each of the wiring patterns prepared above using an optical microscope, and the presence or absence of peeling and residue was confirmed from the obtained observation images. Figure 2The optical microscope image of the wiring pattern of Example 1 is shown in FIG. Moreover, the minimum L / S at which no peeling or residue is confirmed is taken as the resolution. The results are shown in the "Resolution (μm)" column of Table 2. In addition, based on the results, the resolution is evaluated with the following indicators. The results are shown in the "Evaluation of Resolution" column of Table 2.
[0124] “◎”: Resolution (L / S) is 15μm / 15μm.
[0125] “○”: Resolution (L / S) is 20 μm / 20 μm.
[0126] “×”: The resolution (L / S) is 25 μm / 25 μm or more.
[0127] (Comprehensive evaluation)
[0128] Based on the evaluation of the developability and resolution described above, comprehensive evaluation was performed using the following indices. The results are shown in the "Comprehensive Evaluation" column of Table 2.
[0129] “◎”: Both developability and resolution are ◎.
[0130] “○”: One of the developability and the resolution is ○, and the other is ◎ or ○.
[0131] “×”: At least one of the developability and the resolution is ×.
[0132] [Table 2]
[0133]
[0134] Comparative Example 1 is a test example without acrylic resin. As shown in Table 2, in Comparative Example 1, although the development time is overwhelmingly short, peeling occurs when L / S is 25μm / 25μm or less, and the resolution is insufficient. In addition, Comparative Example 3 is a test example in which the ratio of the photopolymerizable compound is higher than that of Comparative Example 1. As shown in Table 2, in Comparative Example 3, although the development time is short, peeling occurs when L / S is 25μm / 25μm or less, and the resolution is still insufficient.
[0135] In addition, Comparative Example 2 is a test example in which a cellulose-based polymer compound is not contained. As shown in Table 2, in Comparative Example 2, the development time is long, and when L / S is 20 μm / 20 μm or less, residue is observed, and the resolution is insufficient. In addition, Comparative Example 4 is a test example in which an acrylic resin d having no acid value (no acid value) is used as an acrylic resin. As shown in Table 2, in Comparative Example 4, the development time is longer than that in Comparative Example 2.
[0136] With respect to these Comparative Examples 1 to 4, when the total amount of the cellulose polymer compound, the acrylic resins a to c having an acid value, and the photopolymerizable compound is set to 100 mass %, Examples 1 to 8 containing the cellulose polymer compound at a ratio of 10 to 40 mass %, the acrylic resins a to c having an acid value at a ratio of 5 to 40 mass %, and the photopolymerizable compound at a ratio of 30 to 60 mass %, compared with Comparative Example 2 not containing the cellulose polymer compound and Comparative Example 4 using the acrylic ester d having no acid value, the development time is relatively short, and the development can be completed within 60 seconds. In addition, in Examples 1 to 8, the generation of peeling and residue is suppressed, and it is suitable for forming a thin line with an L / S of 20 μm / 20 μm or less.
[0137] Among them, when the total of the cellulose polymer compound, the acrylic resins a to c having an acid value, and the photopolymerizable compound is set to 100% by mass, Examples 2, 3, 7, and 8, which contain the cellulose polymer compound at a ratio of 20 to 35% by mass, the acrylic resins a to c having an acid value at a ratio of 10 to 30% by mass, and the photopolymerizable compound at a ratio of 50 to 60% by mass, have particularly excellent developability and resolution. That is, the development time is suppressed to within 45 seconds, which greatly shortens the development time. In addition, it is also suitable for forming ultrafine lines with an L / S of 15μm / 15μm.
[0138] These results demonstrate the significance of the technology disclosed herein.
[0139] As mentioned above, although this invention was demonstrated in detail, these are only examples, and this invention can be variously modified in the range which does not deviate from the summary.
Claims
1. A photosensitive composition comprising: Conductive powder; Cellulose-based organic binders; A (meth)acrylic photocurable resin having an acid value; a photopolymerizable compound; and Photopolymerization initiator, When the total amount of the cellulose-based organic binder, the (meth)acrylic photocurable resin having an acid value, and the photopolymerizable compound is set to 100% by mass, The content ratio of the cellulose-based organic binder is 10 to 40% by mass; The content ratio of the (meth) acrylic photocurable resin having an acid value is 5 to 40% by mass; The content ratio of the photopolymerizable compound is 30 to 60% by mass. The ratio of the (meth)acrylic photocurable resin having an acid value in the entire photosensitive composition is lower than that of the photopolymerizable compound.
2. The photosensitive composition according to claim 1, wherein The cellulose-based organic binder has an acid value of 20 mgKOH / g or more.
3. The photosensitive composition according to claim 1 or 2, wherein The acid value of the (meth)acrylic photocurable resin having an acid value is 50 mgKOH / g or more and 150 mgKOH / g or less.
4. The photosensitive composition according to claim 1 or 2, wherein The weight average molecular weight of the (meth)acrylic photocurable resin having an acid value is 10,000 or more and 30,000 or less.
5. The photosensitive composition according to claim 1 or 2, wherein When the total amount of the cellulose-based organic binder, the (meth)acrylic photocurable resin having an acid value, and the photopolymerizable compound is set to 100% by mass, The content ratio of the cellulose-based organic binder is 20 to 35% by mass; The content ratio of the (meth) acrylic photocurable resin having an acid value is 10 to 30% by mass; The content ratio of the photopolymerizable compound is 50 to 60% by mass.
6. The photosensitive composition according to claim 1 or 2, wherein The conductive powder includes silver-based particles.
7. A composite comprising: green sheets; and A conductive film is disposed on the green sheet and is formed from a dried product of the photosensitive composition according to any one of claims 1 to 6. 8 . An electronic component comprising: a conductive layer formed from a calcined body of the photosensitive composition according to claim 1 .
9. A method for producing an electronic component, comprising the steps of applying the photosensitive composition according to any one of claims 1 to 6 to a substrate, exposing and developing the composition, and then baking the composition to form a conductive layer consisting of a baked body of the photosensitive composition.
